A longitudinal study of the use of rhetorical figures and communicative and stylistic strategies in advertising slogans - Christopher, Anne A. (2009)
This study attempts to analyse developments in the use of rhetorical figures and persuasive strategies in advertising slogans selected from the late 1800s till the beginning of the 21st century. Research has discovered that the use of rhetorical figures, specifically schemes and tropes, in advertising headlines and texts has become more complicated and sophisticated over time. Various persuasive strategies have also been found across different periods. Previous studies have only examined rhetorical figures in isolation rather than a combination of a wide range of figures. Besides, there have not been any studies done on the historical trends of the use of a combination of rhetorical figures. The combination of rhetorical figures in slogans has also not been researched. More significantly, the combination of rhetorical figures and persuasive strategies in advertising slogans has not been examined. A total of 500 advertising slogans were selected from thirteen multinational and established companies and arranged according to the year or decade they were created. The companies selected were ones that existed from the late 1800s or early 1900s and which still exist today. The slogans were then analysed for the presence of schemes and tropes and various persuasive strategies. Two types of analysis were done, that is, a qualitative and a quantitative analysis. The results of the study have revealed changes in the pattern of the rhetorical figures and persuasive strategies employed in advertising slogans through the decades. From the results, a taxonomy has been constructed which can be used to analyse advertising slogans. This taxonomy is a combination of both classical and contemporary approaches, incorporating classical rhetorical figures as well as more contemporary persuasive strategies. The pattern of changes that the results have revealed has also been described.